2018
DOI: 10.1049/iet-rpg.2018.5196
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious frequency control of solar photovoltaic/biogas/biodiesel generator based isolated renewable microgrid using grasshopper optimisation algorithm

Abstract: This work endeavours to propose an approximate mathematical model of a community based renewable microgrid with solar photovoltaic, biogas and biodiesel generators including battery storage for load frequency studies. It becomes a great challenge to coordinate between generation and load demand of the microgrid as the renewable sources are highly unpredictable and nature dependent. To overcome this issue, the responses of the system are studied under different real-world scenarios of renewable source availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 27 publications
0
114
0
Order By: Relevance
“…When a microgrid is islanded, an optimal controller should be designed to minimize the frequency deviations. In recent years, some research works have been reported related to the optimal frequency control issue of an islanded microgrid [7][8][9][10], but most works have focused on proportional-integral-derivative (PID) control method and its different kinds of improved versions based on intelligent optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…When a microgrid is islanded, an optimal controller should be designed to minimize the frequency deviations. In recent years, some research works have been reported related to the optimal frequency control issue of an islanded microgrid [7][8][9][10], but most works have focused on proportional-integral-derivative (PID) control method and its different kinds of improved versions based on intelligent optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…The power generation from available solar irradiance (ÎŚ in kW/m 2 ) in the STP unit depends on the actions of solar collectors, ORC-based heat-exchanger, and steam turbine. 30 So the complete linearised model of proposed ORC-based LFR type STP unit could be expressed as Equation (12). The values for design parameters in Equation (8) could be evaluated using the LFR type STP system data.…”
Section: Orc-based Lfr Type Solar Thermal Power Unitmentioning
confidence: 99%
“…Some of the reported works hitherto biorenewable cogeneration-based isolated hÎźG were discussed on ALFC. [11][12][13][14][15][16][17] The ALFC regulates the active power demand of the grid only, whilst reactive power control is also crucial in real-world paradigm which depends on voltage regulation of the grid with automatic voltage regulator (AVR). 21 Some works are recently reported on combined voltage and frequency control of isolated system in Gupta et al 22 and interconnected multi-area systems in Othman and El-Fergany and Rajbongshi and Saikia 23-26 for a nominal frequency ( f ) of 60 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive power droop slope is included in the objective function, making it more adaptive to different capacity systems. Power sharing and load voltage control is optimized by a distributed control method in [20]. The power coordination and voltage optimization happen parallelly, thus fulfilling the generation-demand gap.…”
Section: Power Quality Controlmentioning
confidence: 99%